2015
DOI: 10.1364/ao.54.001152
|View full text |Cite
|
Sign up to set email alerts
|

Subhertz linewidth laser by locking to a fiber delay line

Abstract: An ultralow-noise, subhertz 1.55 μm erbium-doped fiber laser that is locked on an all-fiber-based Michelson interferometer is presented in this paper. The interferometer uses 500 m SMF-28 optical fiber and an acousto-optic modulator to allow heterodyne detection. By comparing two identical laser systems, a 0.67 (0.21) Hz linewidth beat-note signal is achieved and we obtain fractional frequency instability of 7×10(-15) at short timescales (0.1-1 s). The frequency noise power spectral density of two identical la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Again note that the estimation of our fiber noise is very conservative, and the fiber noise is very likely much smaller. In fact, the fiber noise reported by Dong et al ., is close to the thermal noise limit 22 . Another way to reduce fiber noise is to actively stabilize the fiber to an ultra-low phase noise cw laser.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Again note that the estimation of our fiber noise is very conservative, and the fiber noise is very likely much smaller. In fact, the fiber noise reported by Dong et al ., is close to the thermal noise limit 22 . Another way to reduce fiber noise is to actively stabilize the fiber to an ultra-low phase noise cw laser.…”
Section: Discussionsupporting
confidence: 66%
“…By using intrinsically low phase noise RF oscillators, −100 dBc/Hz at close to carrier frequency is feasible by carefully designing an environmental isolation system such as ref. 22. Note that using intrinsically low phase noise RF oscillators is not very effective in conjunction with other methods for active phase noise suppression, for example based on the use of high harmonics of an EO comb, since the sensitivity is not as good as the present method even when using sidemodes of an EO comb up to a harmonic order of 100 10, 27 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the sources of the noise floor are still in doubt 18,24,25 . Recently, in the experiment for ultra-stable fiber-stabilized laser, Dong et al 8 observed that the frequency noise PSD range from 1 Hz to 100Hz exhibits a 1 f characteristic seems consistent with Duan's theory. In spite of the recent experimental progress, the thermal noise below 30 Hz is still unclear owing to the excess noise sources such as laser noise, electronic noise and environmental noise.…”
mentioning
confidence: 52%
“…In many fiber-based systems, such as interferometric fiber-optic sensors [1][2][3][4] , fiber lasers [5][6][7] , and fiber-delay-line stabilized lasers 8 , the fundamental resolution or frequency stability is limited by the intrinsic thermal noise inside optical fibers. Thus, an experimental and theoretical understanding of the thermal noise in optical fibers is important.…”
mentioning
confidence: 99%